The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1002/cjg2.1512
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Magnetic Fabric of Wenquan Granite Pluton in the Western Qinling Mountains and Implications for Emplacement Mechanism

Abstract: Wenquan pluton is situated in the western Qinling mountains and is adjacent to the south of the Shangdan suture zone. Through analyses of regional tectonics and the anisotropy of low‐field magnetic susceptibility (AMS) together with rock magnetism of 125 oriented samples, the emplacement mechanism of the pluton is studied. The values of most mean susceptibilities (km) show a wide variation range. Thermomagnetic curves demonstrate that the paramagnetic minerals such as biotite, acting as the main magnetic carri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…Besides, the relevant rock magnetism researches (including χ‐T curves, hysteresis loops and IRM) were carried on many other contemporaneity plutons of the Qinling Orogen, such as the Wenquan pluton in West Qinling (Xie et al, 2010), the Laocheng pluton and Yanzhiba pluton in South Qinling (Tao, 2014), the Baliping pluton in East Qinling (Li et al, 2017) and the Mishuling pluton in West Qinling (Liang, Jin, Nantasin, & Zhang, 2015). All the results show that low K m values are determined by paramagnetic minerals, for example, biotite and hornblende, and high K m values is constrained by multidomain (MD) magnetite.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the relevant rock magnetism researches (including χ‐T curves, hysteresis loops and IRM) were carried on many other contemporaneity plutons of the Qinling Orogen, such as the Wenquan pluton in West Qinling (Xie et al, 2010), the Laocheng pluton and Yanzhiba pluton in South Qinling (Tao, 2014), the Baliping pluton in East Qinling (Li et al, 2017) and the Mishuling pluton in West Qinling (Liang, Jin, Nantasin, & Zhang, 2015). All the results show that low K m values are determined by paramagnetic minerals, for example, biotite and hornblende, and high K m values is constrained by multidomain (MD) magnetite.…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic susceptibility is a physical property of materials representing the capacity of the material to be magnetized in a given magnetic field, which is closely related with the type and distribution of magnetic mineral (Tarling et al, 1993;Xie et al, 2010). The mean magnetic susceptibility, κ m , varies widely between 14 and 5625 µSI (Table 1, Fig.…”
Section: Magnetic Susceptibilitymentioning
confidence: 99%
“…7b). The mean magnetic susceptibility (P J ) of a rock is closely related with type and distribution of magnetic minerals (Tarling et al, 1993;Xie et al, 2010), and anisotropy degree (P J ) is jointly controlled by the shape preferred orientation (SPO) of magnetic grain and the lattice preferred orientation (LPO) of magnetic mineral as well as the (Rochette et al, 1999), hence the positive correlation shown in Fig. 7 indicates the controlling factors have similarities in κ m and P J to some degree.…”
Section: T and P Jmentioning
confidence: 99%
“…Inverse magnetic fabric was defined by the K 2 -K 3 plane being parallel to the dyke wall and K 1 axes being nearly perpendicular to it. Following the work of Rochette [7,8], only normal magnetic fabric is considered reliable for inferring magma flow direction [6][7][8][9][10][11][12][13][14][15][16][17][18].…”
mentioning
confidence: 99%